Dynamic MR Imaging of the Temporomandibular Joint Using a Balanced Steady-State Free Precession Sequence at 3T - Yen, P.; Katzberg, R.W.; Buonocore, M.H.; Sonico, J. (American Journal of Neuroradiology, 2013)
SUMMARY: The aim of our project was to develop an MR imaging protocol for dynamic imaging of the TMJ. We imaged a total of 24 joints in 12 subjects. We developed an imaging protocol on a 3T system using the true FISP sequence that yielded an acceptable spatial and temporal resolution for dynamic MR imaging. bSSFPbalanced steady-state free precessionFISPfast imaging with steady-state precessionHASTEhalf-Fourier acquired single-shot turbo spin-echoTMJtemporomandibular joint